Decolonizing the Language of Lutheran Theology: Confessions, Mission, Indians, and the Globalization of Hybridity - Tinker, George E. (Dialog, 2011)
Christianity as we know it in the United States is essentially a european ethnic religious movement, one that has necessitated decolonizing processes as it has spread into the formerly euro-colonized global world. In many ways, lutheranism has been and continues to be even more discretely ethnocentric, based largely in the thinking, the cultures, and the languages of the germanic north. This essay challenges lutheran theologians to begin a dedicated process of decoding the narrowly ethnic and implicitly colonizing language of lutheran theology.